Pengembangan simulasi virtual untuk menurunkan kuantitas miskonsepsi siswa SMA pada topik fluida - Saputra, Oka (Universitas Negeri Surabaya, 2022)
Teachers in learning activities should carry out practicum activities to facilitate students' learning, so there are no misconceptions. The facts in the field say that many teachers still do not do practicum because of the availability of tools and materials at the school, so virtual simulations are needed as a medium in practicum activities. The development model used in this study consists of three stages, namely the definition stage, the design stage, and the development stage. The results showed that the virtual simulation was feasible to use in the learning process. The validation analysis on the developed virtual simulation with very achievable criteria. In the student's opinion, the virtual simulation feasibility with very feasible criteria. Teachers in learning to remediate misconceptions can use the virtual simulation that has been developed.